Carbon Nanomaterials for Tailored Biomedical Applications - Mgbemena, Chinedum Ogonna; Mgbemena, Chika Edith (Asian Review of Mechanical Engineering, 2021)
Carbon Fibre (CF) and Carbon Nanotube (CNT) are typical Carbon nanomaterials that possess unique features which make them particularly attractive for biomedical applications. This paper is a review of the Carbon Fibre (CF) and Carbon Nanotube (CNT) for biomedical applications. In this paper, we describe their properties and tailored biomedical applications. The most recent state of the art in the biomedical application of CFs and CNTs were reviewed.